MENINGKATKAN KREATIVITAS ANAK MELALUI BERMAIN PLAYDOUGH PADA ANAK USIA 4-5 TAHUN DI KB MUTIARA KASIH DESA KOTO PERAMBAHAN KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Astuti, Yani; Isjoni, Isjoni; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase creativity in children aged 4-5 years through playing playdough in KB Desa Mutiara Kasih Village Koto Perambahan District Kampar East Kampar Regency. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years who are 16 children in KB Mutiara Kasih. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that playing playdough can boost creativity in children aged 4-5 years. It can be seen from the increase in the average percentage of the creativity of children in the first cycle by 6 2.2% which is the criteria began to develop (MB) and an increase of 31% in the second cycle to 81.4% which is very good at developing criteria (BSB). So, play playdough can improve creativity of children aged 4-5 years in KB Desa Mutiara Kasih Village Koto Perambahan Kampar East District Kampar Regency.Keywords : Creativity, Playing Playdough